Lean Polycystic Ovary Syndrome: A Narrative Review - Aboubakr Elnashar (IMR Press, 2024)
Objectives: (1) To delineate the differences between lean and obese polycystic ovary syndrome (PCOS). (2) To review different modalities for management of infertility associated with PCOS. Mechanism: Literature review of PubMed from 2000 to 2023. Findings in Brief: Body weight is more important than the Rotterdam phenotype in influencing the metabolic status. Both the lean and obese PCOS groups exhibit individual differences in body composition and other parameters: clinical signs, psychological, hormonal, metabolic, and genetic profiles. Lean PCOS differs from lean non-PCOS regarding metabolic profile, hepatic impairment, and cardiovascular risks. Management: lifestyle modifications serve as first-line therapy, emphasizing weight maintenance with a high caloric intake during breakfast and reduced intake at dinner. Additionally, micronutrients supplementation and resistance exercise are recommended. Induction of ovulation through the administration of as adjunctive therapies letrozole, clomiphene citrate, and metformin may be considered. Laparoscopic ovarian drilling (LOD) may be considered in cases where medical induction of ovulation failed. Intrauterine insemination is associated with promising results. Assisted reproductive techniques (ART) are recommended for women who fail to conceive despite the restoration of ovulation, or when additional factors contribute to their infertility. Conclusions: A significant proportion of patients with PCOS exhibit normal body mass index (BMI). The management of PCOS-associated infertility should be individualized based on the patient's BMI.